Alcohol Portrayal in Selected American Plays - Mushtaq Abdulhaleem Mohammed Fattah (Ilmu Inovasi Nusantara, 2022)
Alcoholism, as a social disease that creeps into society, in general, and into the family, in particular, causes addiction, depression, and ultimately death. Affecting a vast array of people, Alcoholism is indiscriminate regardless of race, gender, identity, education, class, or intelligence. Alcoholism results in societal problems that are depicted heavily on the American stage after wars to reach solutions. A qualitative research method is going to be followed and applied by employing a mixture of Scholarship and Textual Analysis Methods are used to investigate the body of scholarship written about the two playwrights, their literary works, and historical periods. By comparing two American plays: Thornton Wilder’s Our Town (1938) and Eugene O’Neill’s Long Day’s Journey into Night (1955), this paper identifies alcoholism as a social disease, traces back its causes, and analyzes the problematic portrayals of its stereotypes. By following the Block Method, this paper makes a comparison to deal with particular and important features of the two plays for the argument presented, supported by textual evidence taken from both texts. This study raises questions such as: Why is alcoholism projected publicly? How do people feel and react toward alcoholic addicts? Are alcoholic addicts, the main characters in the selected plays, reliable, tragic, sympathetic, or empathetic? Does the playwrights’ history of alcohol play a role in shaping such characters?